A novel AIRE mutation leads to autoimmune polyendocrine syndrome type-1 - Qian, Guofeng; Yan, Xiaoyi; Xuan, Junli; Zheng, Danfeng; He, Zhiwen; Shen, Jianguo (Frontiers in Cell and Developmental Biology, 2022)
Autoimmune polyendocrine syndrome type-1 (APS-1) is a rare inherited monogenic autoimmune disease characterized by the presence of at least two of three following major clinical features: chronic mucocutaneous candidiasis, hypoparathyroidism, and adrenal insufficiency. Mutations in autoimmune regulator (AIRE) gene have been found to contribute to APS-1. In the present study, we reported a 36-yr-old male APS-1 patient who presented with hypoparathyroidism and Addison’s disease. The proband underwent complete clinical examinations and mutation screening was performed by Sanger sequencing on AIRE gene. A novel homozygous mutation in exon 9 of the AIRE gene (c.1024C>T) was identified. Based on sequencing findings, HEK293T cell-based assays were conducted to analyze the subcellular localization and mutant transcript processing. Our results revealed that p.Q342X mutant localized in nuclear speckles and exerted a dominant-negative effect on wildtype AIRE function. We reported the c.1024C>T mutation of AIRE gene for the first time, which enriched the AIRE mutation database and contributed to further understanding of APS-1.